2015
DOI: 10.1002/acn3.200
|View full text |Cite
|
Sign up to set email alerts
|

Torin 1 partially corrects vigabatrin‐induced mitochondrial increase in mouse

Abstract: Recent findings in mice with targeted deletion of the GABA-metabolic enzyme succinic semialdehyde dehydrogenase revealed a new role for supraphysiological GABA (4-aminobutyric acid) in the activation of the mechanistic target of rapamycin (mTOR) that results in disruption of endogenous mitophagy. Employing biochemical and electron microscopic methodology, we examined the hypothesis that similar outcomes would be observed during intervention with vigabatrin, whose antiepileptic capacity hinges on central nervou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 30 publications
2
27
0
Order By: Relevance
“…The current report expands the link between supraphysiological GABA and mTOR signaling described in earlier studies (Lakhani et al 2014; Vogel et al 2015). Until now, drugs that have extended the lifespan of aldh5a1 −/− mice have included taurine, vigabatrin (an irreversible inhibitor of GABA-transaminase), CGP-35348 (a GABA B receptor antagonist), NCS-382 (a GHB receptor antagonist), and the ketogenic diet (Hogema et al 2001; Gupta et al 2002; Nylen et al 2008b).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The current report expands the link between supraphysiological GABA and mTOR signaling described in earlier studies (Lakhani et al 2014; Vogel et al 2015). Until now, drugs that have extended the lifespan of aldh5a1 −/− mice have included taurine, vigabatrin (an irreversible inhibitor of GABA-transaminase), CGP-35348 (a GABA B receptor antagonist), NCS-382 (a GHB receptor antagonist), and the ketogenic diet (Hogema et al 2001; Gupta et al 2002; Nylen et al 2008b).…”
Section: Discussionsupporting
confidence: 82%
“… Recent studies have identified a role for supraphysiological GABA in the regulation of mTOR (mechanistic target of rapamycin), a protein kinase with pleiotropic roles in cellular development and homeostasis, including integration of growth factors and nutrient sensing, and synaptic input in neurons (Lakhani et al 2014; Vogel et al 2015). Aldehyde dehydrogenase 5a1-deficient ( aldh5a1 −/− ) mice, the murine orthologue of human succinic semialdehyde dehydrogenase deficiency (SSADHD), manifest increased GABA that disrupts mitophagy and increases mitochondria number with enhanced oxidant stress.…”
mentioning
confidence: 99%
“…Mice in the Torin 1 study were given intraperitoneal injections of either 5 mg/kg Torin 1 or vehicle treatment every day of the running period (18). Rapamycin and Torin 1 treatments were prepared in a vehicle PBS solution containing 5% polyethylene glycol 400/5% Tween 80 as described previously (17).…”
Section: Methodsmentioning
confidence: 99%
“…Further, long-term treatment with VGB is contraindicated due to marked and permanent visual-field impairments (Singh et al 2013; Froger et al 2014; Good et al 2011; Pellock 2011; Escalera et al 2010; Casarano et al 2011; Matern et al 1996; Al-Essa et al 2000). Of further concern is the predicted expectation that VGB will augment brain GABA (Ergezinger et al 2003; Pearl et al 2014a; 2014b), which is a relevant observation in light of recent studies (described above) highlighting GABA-induced impairment of autophagic processes (Vogel et al 2015). The potential use of mTOR inhibitors (e.g., rapamycin, Torin 1 or 2) along with VGB might be an effective intervention, since this would both decrease production of GHB and clear the oxidative-damaging effects of further-enhanced GABA levels.…”
Section: Treatment Of Ssadhdmentioning
confidence: 99%